The presence of osteocalcin, osteopontin and reactive oxygen species-positive cells in pulp tissue after dental bleaching - Benetti, F. [UNESP]; Briso, A. L.F. [UNESP]; Carminatti, M. [UNESP]; de Araújo Lopes, J. M. [UNESP]; Barbosa, J. G. [UNESP]; Ervolino, E. [UNESP]; Gomes-Filho, J. E. [UNESP]; Cintra, L. T.A. [UNESP] (Wiley, 2019)
Aim: To analyse the influence of H 2 O 2 on pulp repair through osteocalcin and osteopontin immunolabelling and in cellular defence by using the antireactive oxygen species (ROS) antibody. Methodology: The maxillary molars of 50 rats were treated with 35% H 2 O 2 (Ble groups) or placebo gel (control groups). At 0 h and 2, 7, 15 and 30 days (n = 10 hemimaxillae), the rats were killed and pulp tissue was evaluated using inflammation and immunolabelling scores (osteocalcin/osteopontin); ROS-positive cells were counted. Paired t-test and Wilcoxon signed-rank test were used (P < 0.05). Results: The Ble group had necrosis in the coronal pulp at 0 h and in the occlusal third of the coronal pulp at 2 days; at 7, 15 and 30 days, no inflammation was noted similar to the controls (P > 0.05). Osteocalcin was absent in the Ble at 0 h, moderate at 2 days and increased thereafter, differing from the controls at all two periods (P < 0.05). Osteopontin was higher principally at 7 and 15 days in Ble groups, but differing with control groups from 2 days after bleaching (P < 0.05). The Ble group had more ROS-positive cells in the pulp at 7 and 15 days (P < 0.05). Tertiary dentine was observed at 7 days, increasing thereafter (P < 0.05). Conclusions: Post-bleaching pulp repair was associated with increased osteocalcin over time. Osteopontin also participated in this process, and anti-ROS was involved in cellular defence against H 2 O 2 .
Keywords: dental pulp; hydrogen peroxide; osteocalcin; osteopontin; reactive oxygen species; tertiary dentine